Rancang Bangun Sistem Informasi Pendaftaran Murid Baru secara Online pada Purwacaraka Padang - Larissa Navia Rani; Desva Willton (Jurnal KomtekInfo, 2019)
The rapid development of information technology today, triggering all activities in all fields of using technology in carrying out its operational activities without exception Purwacaraka Padang in registering new students. This new online student registration information system is used to make it easier for prospective students to register without having to come directly to Purwacaraka Padang. In addition, with this application the activities carried out can be displayed in this application and provide the latest information to prospective students and the community. The design of this system uses the UML model (Unified Model Language) which can provide an overview of how the program runs and the interaction between actors and systems. In addition, the use of the PHP programming language that is supported by MySQL databases also makes this system an useful online information system.